2022
DOI: 10.1186/s40798-022-00532-w
|View full text |Cite|
|
Sign up to set email alerts
|

A Proposed Conceptual Sport Nutrition Approach for Athlete Development and Assessment: The Athlete Nutrition Development Approach

Abstract: Appropriate dietary intake can improve athletes’ health and sport performance and is a direct result of eating behaviours. Therefore, assessing and shaping athletes’ eating behaviours and dietary intake is critical to the provision of sport nutrition services. As such, nutrition practitioners must also consider the determinants of eating behaviours. However, dietary intake, eating behaviours, and its determinants are inconsistently defined in the literature, requiring nutrition practitioners to navigate a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Adopting an appropriate nutritional approach is demonstrably linked to both enhanced health and improved athletic performance in athletes. Studies by O’Brien, Collins & Amirabdollhian (2021) and Iwasa-Madge & Sesbreno (2022) have revealed a direct correlation between athletes’ nutritional styles and outcomes in both health and sporting settings. Recognizing the critical role of nutrition in athletic success, Finamore et al (2022) emphasizes the compelling need for research aimed at bolstering the nutritional knowledge of sports participants.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting an appropriate nutritional approach is demonstrably linked to both enhanced health and improved athletic performance in athletes. Studies by O’Brien, Collins & Amirabdollhian (2021) and Iwasa-Madge & Sesbreno (2022) have revealed a direct correlation between athletes’ nutritional styles and outcomes in both health and sporting settings. Recognizing the critical role of nutrition in athletic success, Finamore et al (2022) emphasizes the compelling need for research aimed at bolstering the nutritional knowledge of sports participants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, research on nutrition education for athletes focusing on motivation has attracted attention in a broad range of sports. The formation of athletes’ eating behaviors and assessment of dietary intake is very important because an appropriate dietary intake improves athletes’ health and sports performance [ 14 ]. However, few studies have investigated deeper associations.…”
Section: Introductionmentioning
confidence: 99%
“…Besides following a proper exercise regime with correct techniques, a balanced nutrition is also essential (Farhud, 2015). The main dietary goal for gymnasium users is to have proper nutrition to ensure optimum health, fitness, performance, and also to promote healthy dietary practices in the long term (Iwasa-Madge & Sesbreno, 2022;Purcell, 2013). It has been reported that nutrient deficiency can negatively affect health and performance of an individual (Saunders & Smith, 2010).…”
Section: Introductionmentioning
confidence: 99%